2017
DOI: 10.1126/sciadv.1601741
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and laser-reconfigurable 2D heterocrystals obtained by epitaxial stacking of crystallographically incommensurate Bi 2 Se 3 and MoS 2 atomic layers

Abstract: Heterocrystals: rotationally oriented stacks of incommensurate 2D materials with tunable and laser-reconfigurable properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 69 publications
(97 reference statements)
8
70
0
Order By: Relevance
“…[83] The relevant crystal structures are shown in Figure 8g-j. [83] The relevant crystal structures are shown in Figure 8g-j.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 2 more Smart Citations
“…[83] The relevant crystal structures are shown in Figure 8g-j. [83] The relevant crystal structures are shown in Figure 8g-j.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…The reason for the PL intensity suppression is that the band structure turns to an indirect nature. [83] Copyright 2017, The Authors, Published by American Association for the Advancement of Science. The optical transmittance spectra of isolated MoS 2 and the MoS 2 /n-Bi 2 Se 3 vdWH indicated that the optical transmittance continuously decreases with increasing Bi 2 Se 3 layers (as shown in Figure 9b).…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kar et al found that MoS2-Bi2Se3 shows a different electronic band structure. [106] MoS2 is grown by sulfurization of MoO3 at first, then Bi2Se3 is grown on MoS2 at 480 ℃ with Bi2Se3 powder placed on the hot zone of the furnace. The thickness is controlled by changing deposition time.…”
Section: Vertical Heterostructurementioning
confidence: 99%
“…[106] Such a heterostructure shows novel properties including 100% photoluminescence (PL) quenching, transmittance edge modulation (1.1 to 0.75 eV), suppressed Raman modes and broad band evolution of spectral transmittance. [106] Attractively, these characters can be reconfigured through a focused laser and the tunable nature of the heterostructure expands future electronic and optoelectronic applications. Except for combination between TMDs, separately grow TMDs and other layered materials is effective to form heterostructures.…”
Section: Vertical Heterostructurementioning
confidence: 99%